INISIASI POSYANDU REMAJA SEBAGAI PENCEGAHAN ANEMIA REMAJA PUTRI DI PUSKESMAS MLATI II KABUPATEN SLEMAN - Muhamad Almas Radifan; Mubasysyir Hasanbasri (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
There are several adolescent girls who have experienced anemia in villages around Puskesmas Mlati II, especially at the junior high school level, 21.03% of a total of 233 students in January 2020, which is before the COVID-19 pandemic. The prevalence of anemia is expected to increase after the pandemic. The main factors are the habit of not eating breakfast, poor diet, and lack of adolescent health services. The poverty factor in the family and the irregular distribution of blood supplement tablets are the drivers of the problem of anemia. As for the prevention of the problem of anemia of adolescent girls in the villages around the Puskesmas Mlati II area, the PKPR and nutritionist plan to establish adolescent posyandu in each hamlet. It is hoped that the initiation of the adolescent posyandu will not only carry out posyandu with five tables, but can also include other additional programs such as educational webinars, online peer education, shared breakfast practices, and permaculture nutrition garden practices. The purpose of this activity is to create an adolescent posyandu as one of the efforts of adolescent girls' health services in preventing anemia. The results of this activity are in the form of a description of the urgency of adolescent posyandu for the health of adolescent girls and the initiation of the adolescent posyandu itself, such as situation analysis of the problem of anemia, planning of program implementation, including the formation of adolescent cadres, and preparing a draft evaluation document.